Neccessity for Methodology for Identification of Fringe Areas Having Potentiality to Form a City Region - Poorva, Ar.; Banerjee, Subhrajit (Journal of Neonatal Surgery, 2025)
As the urban areas are overspilling beyond their carrying capacity in terms of population the growth of the city tends towards Peri-Urban or fringe areas. These fringe areas are naturally converting to a dynamic transformation zone have enormous potential to play a positive role in enhancing urban sustainability at regional and global level. In the similar line of thought, SDG 11.A aims at supporting positive economic, social and environmental links between urban and peri-urban to strengthen Regional and National planning. The challenge of integrating fringe areas to city-region aims to overcome the differences of approach of Urban and Rural planning, utilizing the fringe potentiality and functions to achieve multifunctionality. Development potentiality, which refers to opportunities and possibilities for growth, progress and improvement from various perspectives, including social, economic, environmental and infrastructural development, is the inherent ability or capacity of a region or area for positive and sustainable development. This research paper aims at ascertaining the need for methodology for identifying the fringe areas that are having a potentiality to form a region.